Impact of having surplus blastocysts cryopreserved on the ongoing pregnancy rate following a fresh transfer - Rui Wu; Zhuo Chen; Wenfang Xu; Chao Yang; Hua Zhou; Wenjie Xu; Guanyou Huang; Shuyun Zhao (Taylor & Francis Group, 2023)
Purpose This study aimed to investigate whether a surplus of vitrified blastocysts correlated with ongoing pregnancy by analyzing the clinical outcomes of fresh transfer cycles with/without a surplus of vitrified blastocysts.Methods This was a retrospective analysis carried out in the Reproductive Medicine Center of Guizhou Medical University Affiliated Hospital between January 2020 and December 2021. Overall, 2482 fresh embryo transfer cycles were included in this study, including 1731 cycles with a surplus of vitrified blastocysts (group A) and 751 cycles with no surplus of vitrified blastocysts (group B). The clinical outcomes of fresh embryo transfer cycles were analyzed and compared between the two groups.Results In total, the clinical pregnancy rate (CPR) and ongoing pregnancy rate (OPR) after fresh transfer in group A were significantly higher than those in group B (59% vs. 34.1%, p < .001; 51.9% vs. 27.8%, p < .001, respectively). Moreover, the miscarriage rate was significantly lower in group A when compared to that in group B (10.8% vs. 16.8%, p = .008). When grouped by either female age or the number of good-quality embryos transferred, the same trends for CPR and OPR were seen in all subgroups. After adjusting for potential confounding factors in multivariate analysis, a surplus of vitrified blastocysts remained significantly associated with a higher OPR (OR: 1.52; 95% CI:1.21-1.92).Conclusion Ongoing pregnancy outcome increases significantly in fresh transfer cycle with a surplus of vitrified blastocysts.